An observational study of factors associated with dengue outcomes in intensive care unit / See Chang Seng - See, Chang Seng (2019)
In Malaysia, dengue fever is one of the major public health problem which has had significant impact on socio-economic and health resources especially when involving intensive care unit (ICU) stay. This study aimed to determine the factors associated with outcomes in those dengue patients who admitted to ICU. This was a retrospective observational study of patients in a tertiary level state hospital in Malaysia, between Jan 1 and Dec 31 2017. Patients with confirmed dengue diagnosis were stratified into 2 groups based on ICU stay (≤ 3 days or > 3 days) and mortality (fatal and non-fatal cases). Socio-demographic, clinico-laboratory data and therapeutic parameters between these groups were compared by using appropriate statistical analysis method. Total 140 patients were included in this study with mean length of ICU stay 3.79+2.47 days. Mortality rate among these patients was 7.8% and prolonged stay was seen in 36.4% studied patients. Factors including age > 50 years old, pre-existing diabetes mellitus and hypertension, higher number of co-morbidities, prolonged prothrombin time and activated partial thromboplastin time, thrombocytopenia, hypoalbuminemia, increased creatinine, alanine aminotransferase and aspartate aminotransferase level, and dialysis support were common seen in non-survivors. However, multiple logistic regression analysis showed only number of co-morbidities (OR 2.6, 95% CI 1.26 to 5.38, p-value 0.009) and aspartate aminotransferase (AST) level (OR 1.0, 95% CI 1.0-1.01, p-value 0.001) were found independently significant factors associated with dengue mortality. Meanwhile, patients having severe dengue, pre-existing blood disorder, increased number of co-morbidities, renal impairment, mild thrombocytopenia, required intubation or inotropic support were significantly associated with prolonged ICU stay. However, only female gender (OR 0.36, 95% CI 0.14 to 0.90, p-value 0.029) and elevation of activated partial thrombin time iv 2 times above normal value (OR 0.11, 95% CI 0.02 to 0.66, p-value 0.015) were found to be independently significant related to ICU stay duration. In conclusion, early recognition of risk factors associated with prolonged ICU stay and mortality among dengue fever patients can help in early decision making for ICU admission. Hence early aggressive care and organ support from ICU on higher risk patients can help in decreasing dengue morbidity and mortality.